Prognostic Significance of Preoperative Neutrophil-Lymphocyte Ratio in Vascular Surgery: Systematic Review and Meta-Analysis. (November 2020) - Jackson, Sarah M.; Perry, Luke A.; Borg, Carla; Ramson, Dhruvesh M.; Campbell, Ryan; Liu, Zhengyang; Nguyen, Jacqueline; Douglas, Ned; Kok, Juliana; Penny-Dimri, Jahan
Objective: The global burden of surgical vascular disease is increasing and with it, the need for cost-effective, accessible prognostic biomarkers to aid optimization of peri-operative outcomes. The neutrophil-lymphocyte ratio (NLR) is emerging as a potential candidate biomarker for perioperative risk stratification. We therefore performed this systematic review and meta-analysis on the prognostic value of elevated preoperative NLR in vascular surgery. Methods: We searched Embase (Ovid), Medline (Ovid), and the Cochrane Library database from inception to June 2019. Screening was performed, and included all peer-reviewed original research studies reporting preoperative NLR in adult emergent and elective vascular surgical patients. Studies were assessed for bias and quality of evidence using a standardized tool. Meta-analysis was performed by general linear (mixed-effects) modelling where possible, and otherwise a narrative review was conducted. Between-study heterogeneity was estimated using the Chi-squared statistic and explored qualitatively. Results: Fourteen studies involving 5, 652 patients were included. The overall methodological quality was good. Elevated preoperative NLR was associated with increased risk of long-term mortality (HR 1.40 [95%CI: 1.13-1.74], Chi-squared 60.3%, 7 studies, 3, 637 people) and short-term mortality (OR: 3.08; 95%CI: 1.91-4.95), Chi-squared 66.59%, 4 studies, 945 people). Outcome measures used by fewer studies such as graft patency and amputation free survival were assessed via narrative review. Conclusions: NLR is a promising, readily obtainable, prognostic biomarker for mortality outcomes following vascular surgery. Heterogeneity in patient factors, severity of vascular disease, and type of vascular surgery performed renders direct comparison of outcomes from the current literature challenging. This systematic review supports further investigation for NLR measurement in pre-vascular surgical risk stratification. In particular, the establishment of a universally accepted NLR cut-off value is of importance in real-world implementation of this biomarker.